Belis Sebagai Simbolisasi Penghargaan Terhadap Manusia Dalam Kebudayaan Manggarai: Perspektif Armada Riyanto - Turut, yonesmus; F.X. Eko Armada Riyanto (STIPAS St. Sirilus Ruteng, 2024)
The focus of this article is to discuss belis as a symbol of respect for humans from Armada Riyanto's perspective. The role of belis in raising human dignity, especially women in Manggarai, is very crucial and can change the way society views belis itself. The purpose of this article is to explore the meaning of belis and its role in elevating human dignity seen from the perspective of Armada Riyanto's relational philosophy, especially looking at relationships and dignity. Literature review and literature study methods to explore sources that are closely related to this article and to analyze the belis culture that developed in Manggarai culture. The author collected it from various sources such as online journals, books, essays, theses and many others. The research results show that the belis culture in Manggarai is seen as a means of creating equality and the highest respect for human dignity, especially women, and as a means of elevating the dignity of women as God's creation. Apart from that, the author also found that this belis culture is closely related to what Armada Riyanto discusses in his book Becoming Loving Everyday Theological Philosophy and Relationality namely, when discussing the Manggarai belis culture, it can be seen that relations between humans in the context of belis involve significant social and cultural values, such as appreciation for cooperation, respect for the role of women, and awareness of family values. This understanding shows the uniqueness of the humanistic concept of nature, where the importance of paying attention to the dignity and essence of each individual is the main thing in every interaction.